Stakeholder Recommendations to Refine the Fitness-to-Drive Screening Measure - Sherrilene Classen PhD, MPH, OTR/L, FAOTA; Sandra M. Winter PhD, OTR/L; Craig A. Velozo PhD, OTR/L; Elizabeth M. Hannold PhD (Scholarworks @ WMU, 2013)
In developing the web-based Fitness-to-Drive Screening Measure (FTDS) and keyform (results output) for use to identify at-risk older drivers, we examined the needs, perspectives, and suggestions of three stakeholders groups: occupational therapy practitioners, certified driver rehabilitation specialists (CDRSs), and family members/caregivers. We conducted three focus groups, which were moderated, recorded, transcribed, and analyzed using directed content analysis. Respondents in two focus groups also rated FTDS aspects (e.g., ease of use, format, and relevance), using a visual analog scale (VAS, 0-10 scale with 10 being excellent). All three stakeholder groups contributed to the development of the web-based FTDS. Results from occupational therapy practitioners addressed face validity, appearance, wording, and usability; CDRSs informed follow-up recommendations; and family members/caregivers provided keyform feedback. High VAS ratings (> 7 on 1-10 scale) from the CDRSs (8.4, SD+0.8) and family members/caregivers (9.01, SD+1.02) indicated FTDS acceptability. Overall, our findings support the measure's utility and acceptability among these users. As such, the FTDS may position family members/caregivers to identify at-risk older drivers, facilitate targeted discussions of driving difficulty among occupational therapists and their clients, and afford OT-CDRS an entry point for intervention and clinical decision making.